Impact of hydrogenation conditions on the temperature and strain coefficients of type 1 and typela dual grating sensors - Kalli, Kyriacos; Simpson, George D.; Zhou, Kaiming (My University, 2005)
We report experimental findings for tailoring the temperature and strain coefficients of Type 1 and Type 1A fibre Bragg gratings by influencing the photosensitivity presensitisation of the host optical fibre. It is shown that by controlling the level of hydrogen saturation, via hot and cold hydrogenation, it is possible to produce gratings with lower thermal coefficients. Furthermore, there is a larger difference between the Type 1 and Type 1A thermal coefficients and a significant improvement in the matrix condition number, which impacts the ability to recover accurate temperature and strain invariant data using the Type 1-1A dual grating sensor.
Keywords: Bragg gratings; Optical fibers; Hydrogenation; Fibers